Synchronizing estrus in beef heifers - Heersche, G.; Kiracofe, G.H.; McKee, R.M.; Morrison, D.G. (Kansas State University. Agricultural Experiment Station, 2011)
Estrous synchronization would benefit the cattle industry. Successful methods are not commercially available, so new compounds and treatment procedures are being tested. Treatment with melengestrol acetate, prostaglandin, or luteining releasing factor resulted in unsuccessful synchronization and lowered fertility. Successful synchronization and 63.2% first service conception followed syncro-mate B, PGF2, and LRF.
Keywords: Beef; Synchronization; Melengestrol acetate; Prostaglandin; Fertility